(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate the positive solutions for Hilfer fractional differential equation boundary value problems at resonance. First, we give the expression of the solution with Mittag-Leffler function. Next, we obtain the existence of the positive solutions by using fixed point index theorem. Finally, we give relevant examples to prove our main results.